2014
DOI: 10.1586/14787210.2014.948422
|View full text |Cite
|
Sign up to set email alerts
|

The HIV care cascade and antiretroviral therapy in female sex workers: implications for HIV prevention

Abstract: To achieve viral suppression and fully benefit from antiretroviral therapy (ART), it is important that individuals with HIV know that they are HIV infected, link to and remain in HIV care, start and remain on ART and adhere to treatment. In HIV epidemics where female sex workers (FSWs) are key drivers of HIV transmission, the extent to which FSWs use ART and engage in the HIV care cascade could have a considerable impact on HIV transmission from FSWs to the wider population. In this article we review the spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 93 publications
1
21
0
Order By: Relevance
“…HIV epidemics among FSWs differ between and within countries, and likewise national approaches to scale up of HIV prevention and treatment services should consider context-specific epidemic dynamics and barriers to care 25. We found that an estimated 61.5% of FSWs in the NMBM are living with HIV, which is consistent with the countrywide estimate of 60% and numbers reported from other metropolitan cities in South Africa 1 13.…”
Section: Discussionsupporting
confidence: 84%
“…HIV epidemics among FSWs differ between and within countries, and likewise national approaches to scale up of HIV prevention and treatment services should consider context-specific epidemic dynamics and barriers to care 25. We found that an estimated 61.5% of FSWs in the NMBM are living with HIV, which is consistent with the countrywide estimate of 60% and numbers reported from other metropolitan cities in South Africa 1 13.…”
Section: Discussionsupporting
confidence: 84%
“…A recent review[73] addressing each step of the HIV care cascade among FSWs found that while a number of studies assessed HIV testing among FSWs, almost none evaluated linkage to care and very few addressed retention or adherence. A systematic review and meta-analysis[74**] by the same team assessed ART uptake, attrition and adherence among FSWs and found the following pooled estimates: 37.9% (95% CI: 28.5–48.4%) of HIV+ FSWs were currently on ART, adherence was 76.2% (95% CI: 67.8–83.0%), viral suppression was 57.4% (95% CI: 45.7–68.2%), and 22.2% (95% CI: 5.0–66.4%) of FSWs started ART below 200 CD4+ cells/mm 3 .…”
Section: Cascade Outcomes In Key Populationsmentioning
confidence: 99%
“…ART adherence can significantly maintain or restore immune function while also reducing viral load and the likelihood for onward transmission (Cohen et al, 2011; Grinsztejn et al, 2014; Group et al, 2015). The numerous benefits of ART are, however, reliant on successful engagement in HIV care and treatment, including linkage to care shortly after HIV diagnosis, retention in pre-ART care, timely initiation onto ART, and optimal ART adherence for viral suppression (Gardner, McLees, Steiner, Del Rio, & Burman, 2011; McNairy & El-Sadr, 2012; Mountain et al, 2014b). FSW living with HIV must be linked to care and initiate treatment to receive the individual immunological and clinical benefits of ART, such as viral suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, prevalence data is limited on linkage and retention in HIV care prior to ART initiation (Mountain et al, 2014b). A recent meta-analysis of HIV care continuum estimates that among FSW living with HIV, ART initiation ranges from 19% in Kenya to 48% in Rwanda and current ART use ranging from 23% in Kenya to 70% in Burkina Faso (Mountain et al, 2014a; Mountain et al, 2014b). Strategies that enhance linkage and retention to HIV care, initiation of ART, and viral suppression through ART adherence are urgently needed to maximise the benefits of ART among this key population.…”
Section: Introductionmentioning
confidence: 99%